Peningkatan Pengetahuan Hormonal dan Kesehatan Reproduksi Remaja Perempuan melalui Ruang Diskusi Personal - Ika Friscila; Muhammad Rizali; M. Arief Wijaksono (Lembaga Pengembangan Kinerja Dosen, 2026)
Limited Knowledge Among Adolescent Girls Regarding Hormonal Changes And Reproductive Health, Along With The Strong Influence Of Myths And Social Taboos, Often Leads To Hesitation And Lack Of Openness In Discussing Issues Related To Menstruation And The Fertile Period. This Community Service Activity Aimed To Enhance Adolescent Girls’ Knowledge Of Hormonal Changes And Reproductive Health Through A Personal Discussion Space Approach. The Method Employed Was Participatory Health Education, Beginning With A Brief Educational Session Followed By Small-Group Discussions And Confidential, Non-Judgmental Personal Consultations. The Activity Involved 80 Female Students, Of Whom 47 (58.75%) Utilized The Personal Consultation Sessions. The Results Indicated That Most Questions Raised Were Related To Prevailing Myths And Community Practices Regarding Menstrual Restrictions, Dysmenorrhea, And Misconceptions About The Fertile Period. The Personal Discussion Space Approach Proved Effective In Increasing Adolescents’ Openness, Correcting Misconceptions, And Strengthening Participants’ Understanding Of Hormonal And Reproductive Health. In Conclusion, The Personal Discussion Space Represents An Appropriate And Effective Educational Approach And Is Recommended For Sustainable Implementation To Improve Reproductive Health Awareness Among Adolescent Girls.